The (hidden) role of the EU in housing policy: the Portuguese case in multi-scalar perspective - Allegra, Marco (2020)
Doling (2006, A European Housing Policy? European Journal of Housing Policy, 6(3), 335–349. doi:10.1080/14616710600973169) characterized the intervention of the EU in the field of housing as a ‘stealth policy’, arguing that while the EU has no formal competence in this policy area, it has de facto conditioned national housing policies. This suggests that housing policy is a particularly interesting case for the study of formal and informal modes of multilevel governance. However, European comparative studies about housing policy have almost exclusively focused either on the national or local characteristics of housing systems. In this paper we explore the connections between the development of Portuguese housing policies in the last four decades, on the one side, and EU programmes and documents on the other. We will show how the dynamics of Portuguese housing policy reflected the fluctuations of EU agenda. In doing so, we aim at (i) exploring the history of EU ‘stealth housing policy’ in a moment of re-emergence of housing as a defining theme of EU agenda; and (ii) providing a more accurate characterization of domestic recent general trends and processes through a multi-scalar gaze.